The Profile of Continuing Lecturer Professional Competency Conditions in Private Universities - Yohamintin, Yohamintin; Permana, Johar; Nurdin, Diding; Sururi, Sururi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This research is motivated by the need for the world of education for quality human resources to improve the quality of education. Lecturer competency development has yet to receive special attention to enhance lecturer professional competency. There is no coordinated lecturer competency management strategy supported by policies and program planning for sustainable lecturer professional competency development. The research aims to find a complete picture of the condition of continuing lecturer professional competence. This research is qualitative research with a case study method. Data collection was carried out using interview instruments, observation guidelines, and document review guidelines. The research was conducted at the PGSD Study Program, Bhayangkara Jakarta Raya University. Participants were the study program head, deputy dean for HR, Dean, Head of the Faculty Lecturer Department, and PGSD Lecturer. The results of the study found that: a) the productive age of lecturers, funding for policy development and support is a strength; b) the weakness of the absence of head lecturers and professors and 50% of the academic qualifications are not by their knowledge; c) opportunities for university and foundation support in the development of tri dharma; d) the threat of competition in lecturer recruitment and human resource investment from other better institutions. Recommendations, it is necessary to focus on human resource investment in the long term to improve academic qualifications and sustain the lecturers' professional competence.